PENGARUH DANA DESA TERHADAP KESEMPATAN KERJA DAN TINGKAT KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI - Agustini, Ni Kadek Bella Kurnia; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The government since 2015 has disbursed village funds sourced from the APBN in order to improve development performance in villages including poverty alleviation, village funds transferred through the district / city APBD, which will later be used for infrastructure development such as roads in villages, schools, health facilities for use. reduce the level of poverty, open up jobs and make the community prosperous. The objectives of this study were (1) to analyze the effect of village funds on job opportunities in the regencies / cities of Bali Province, (2) to analyze the effect of village funds and job opportunities on poverty levels in districts / cities of Bali Province, (3) to analyze the indirect effect of funds. villages against poverty levels through employment opportunities in the regencies / cities of Bali Province. The data used in this study are secondary data obtained from the Bali Provincial and Village Empowerment Service and the Bali Province Central Statistics Agency in 2015-2018. The data analysis technique used in this study is path analysis. The results of this study indicate that (1) village funds have a positive and significant effect on job opportunities, (2) village funds and job opportunities have a negative and significant effect on poverty levels, and (3) job opportunities are an intervening variable, the effect of village funds on poverty levels in Regency / City of Bali Province. Keywords : village funds, job opportunities, poverty level.